Valorization of Waste Orange Peels: Aqueous Antioxidant Polyphenol Extraction as Affected by Organic Acid Addition - Dimitris Kalompatsios; Vassilis Athanasiadis; Dimitrios Palaiogiannis; Stavros I. Lalas; Dimitris P. Makris (Beverages, 2022)
Waste orange peels (WOP) are a food processing residue rich in bioactive polyphenols. However, data on aqueous extraction processes for efficient polyphenol recovery are rather limited. The present study dealt with the optimization of WOP polyphenols, using a batch stirred-tank mode and water as solvent. After a preliminary single-factor examination, the implementation of response surface methodology revealed that optimum extraction time and temperature were 60 min and 55 °C, respectively. Under these conditions, the extraction afforded a total polyphenol yield of 26.13 ± 0.78 mg gallic acid equivalents per g dry mass. The use of aqueous solutions of citric, tartaric and lactic acid showed that total polyphenol yield may be significantly increased with 1% tartaric acid or equally with 2.5% citric acid. However, the effect on individual polyphenolic constituents was rather negligible, as determined by high-performance liquid chromatography. The discrepancies observed in the antioxidant properties of the extracts produced with water and acidified water were putatively attributed to some differences in the polyphenolic composition. The extraction methodology proposed is environmentally green and of low cost, and it could certainly be used as an effective means of recovering WOP polyphenols.